114k views
1 vote
Write the expression as a product:

1–(2x–1)^2

User Nunchucks
by
5.7k points

1 Answer

2 votes

Answer:


1- ( { 2 x - 1)}^(2) = 4x (1 - x )

Explanation:

We want to to rewrite


1 - ( { 2 x - 1)}^(2)

Use difference of two squares to get:


{a}^(2) - {b}^(2) = (a + b)(a - b)

This implies that:


{1}^(2) - ( { 2 x - 1)}^(2) = (1 +( 2x - 1))(1 - (2x - 1))


{1}^(2) - ( { 2 x - 1)}^(2) = (1 + 2x - 1)(1 - 2x + 1)

This finally simplifies to:


{1}^(2) - ( { 2 x - 1)}^(2) = 2x (2 - 2x )

Therefore the required product is


2x (2 - 2x ) = 4x(1 - x)

User Stevemarvell
by
5.8k points